2018
DOI: 10.3390/min8010017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mica and Hematite (001) Surfaces on the Precipitation of Calcite

Abstract: Abstract:The substrate effect of mica and hematite on the nucleation and crystallization of calcite was investigated using scanning electron microscope (SEM), X-ray diffraction (XRD), and electron backscatter diffraction (EBSD) methods. On mica, we found, in the absence of Mg 2+ , the substrates' (001) surfaces with hexagonal and pseudo-hexagonal two-dimensional (2-D) structure can affect the orientation of calcite nucleation with calcite (001)~// mica (001) and calcite (010)~// mica (010) to be the major inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…The SEM and TEM images show that dolomite is specifically attached to flaky amorphous mixedlayer illite-smectite (Figs 9 and 11), where no biotic evidence has been observed. Considering that the association of dolomite or Mg-bearing calcite with illite/smectite has been previously reported in the geological record, modern lakes and laboratory experiments (D ıaz-Hern andez et al, 2013;Cuadros et al, 2016;Wanas & Sallam, 2016;Nyiro-K osaa et al, 2018;Xu et al, 2018;Liu et al, 2019;Sanz-Montero et al, 2019), it is here assumed that clay minerals can provide favourable surfaces for dolomite precipitation.…”
Section: Role Of the Clay Surfaces On Dolomite Nucleationmentioning
confidence: 92%
See 1 more Smart Citation
“…The SEM and TEM images show that dolomite is specifically attached to flaky amorphous mixedlayer illite-smectite (Figs 9 and 11), where no biotic evidence has been observed. Considering that the association of dolomite or Mg-bearing calcite with illite/smectite has been previously reported in the geological record, modern lakes and laboratory experiments (D ıaz-Hern andez et al, 2013;Cuadros et al, 2016;Wanas & Sallam, 2016;Nyiro-K osaa et al, 2018;Xu et al, 2018;Liu et al, 2019;Sanz-Montero et al, 2019), it is here assumed that clay minerals can provide favourable surfaces for dolomite precipitation.…”
Section: Role Of the Clay Surfaces On Dolomite Nucleationmentioning
confidence: 92%
“…Recently, the potential effect of clay surfaces (for example, amorphous clay, smectite and palygorskite) on proto-dolomite (Liu et al, 2019) and Mg-rich calcite precipitation (Nyiro-K osaa et al, 2018) has been studied. Based on field observation in soils (D ıaz-Hern andez et al, 2013(D ıaz-Hern andez et al, , 2018Cuadros et al, 2016), evaporative lakes (Wanas & Sallam, 2016) and caves (P erez et al, 2015), as well as laboratory experiments (Xu et al, 2018;Liu et al, 2019) and molecular dynamics (MD) simulations (Sakuma & Kawamura, 2009), it is hypothesized that clay minerals can not only promote the incorporation of Mg 2+ ions into the structure of the rhombohedral carbonate, but also facilitate the local supersaturation of solutes. Moreover, the intimate structural relationship between Mg-bearing calcite and clay minerals in modern calcareous lake indicates that the clay minerals may act as a suitable adsorption surface for primary Ca-Mg carbonate nucleation (Nyiro-K osaa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mg 2+ is known to have an inhibitory effect on calcite crystallization (Niedermayr et al, 2013), and the Mg 2+ /Ca 2+ ratio employed in most of our model solutions (2.3) would favor the concurrent precipitation of metastable aragonite and calcite (Sun et al, 2015). However, in experimental studies the presence of a suitable substrate was found to alleviate the inhibitory effect of Mg 2+ on calcite crystallization (Xu et al, 2018), consistent with our observations of clay-attached calcite particles (and the absence of aragonite) in Lake Balaton at relatively high (up to 4) Mg 2+ /Ca 2+ ratios in lakewater (Nyirő-Kósa et al, 2018). Based on our simulations, the nature of this "substrate effect" is unclear; a visual inspection of the interfaces between montmorillonite and anchored clusters did not show any specific orientation relationships; thus, at the timescales of our model runs no templating effect was apparent.…”
Section: Discussionmentioning
confidence: 86%
“…Sheet silicates, particularly clay minerals, typically occur in the same natural environments where calcite precipitation occurs. Experimental studies suggest that the presence of mica can enhance carbonate nucleation rates (Li et al, 2014), and that calcite nucleation is templated by certain crystal surfaces of mica (Xu et al, 2018). In addition, clays from the smectite group have been found to enhance calcite precipitation (Kralj and Vdović, 2000) and to catalyze the formation of high-magnesian calcite or protodolomite (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction energies of IPETC, H 2 O, and OH − with chalcopyrite (112) and galena (100) surfaces are shown in Table 1. The interaction energies of reagent and minerals are all negative [25,26]. The interaction energies of IPETC with chalcopyrite and galena are −29.7839 kJ/mol and −47.3861 kJ/mol, respectively.…”
Section: Simulationsmentioning
confidence: 96%